2021
DOI: 10.1111/jocs.15334
|View full text |Cite
|
Sign up to set email alerts
|

Does the anthropometric profile influence infection morbidity after coronary artery bypass grafting?

Abstract: Background Infection after cardiovascular surgery is multifactorial. We sought to determine whether the anthropometric profile influences the occurrence of infection after isolated coronary artery bypass grafting (CABG). Methods Between January 2011 and June 2016, 1777 consecutive adult patients were submitted to isolated coronary artery bypass grafting. Mean age was 61.7 ± 9.8 years and 1193 (67.1%) were males. Patients were divided into four groups according to the body mass index (BMI) classification: under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…One explanation for this paradox is that patients with higher BMI may have a lower postoperative bleeding volume and transfusion rate; thus, such patients may save blood products during on-pump CABG factor that contributes to higher survival rates (14). On the other hand, sternal wound infections are more prevalent in obese patients and prior studies have shown increased morbidity and mortality rates in obese patients (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…One explanation for this paradox is that patients with higher BMI may have a lower postoperative bleeding volume and transfusion rate; thus, such patients may save blood products during on-pump CABG factor that contributes to higher survival rates (14). On the other hand, sternal wound infections are more prevalent in obese patients and prior studies have shown increased morbidity and mortality rates in obese patients (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…It brings huge obstacles to the work and spirit of patients, as well as huge economic burden and labor loss to families and society [10]. Therefore, how to effectively promote the recovery of lung function of patients is also the focus of clinical intervention [11,12]. By analyzing the factors affecting pulmonary infection in patients undergoing CABG and proposing nursing measures and invasive examination methods, the occurrence of pulmonary infection can be further reduced.…”
Section: Introductionmentioning
confidence: 99%